Preparation method of perovskite battery

Through multi-step cyclic evaporation and additive treatment methods, the crystal quality and thickness of the perovskite film are improved, and the problem of insufficient thickness of the perovskite film in the prior art is solved, thereby achieving efficient indoor light conversion and carrier diffusion.

CN119562734AInactive Publication Date: 2025-03-04CHINA NAT PETROLEUM CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311126329.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to prepare high-thick perovskite films in the prior art, resulting in low indoor light conversion efficiency and insufficient carrier diffusion length to meet the demand for thick films.

Method used

A multi-step cyclic evaporation method is adopted, including evaporating the CsPbI2Br film on the electron transport layer or the hole transport layer, followed by immersion in the additive solution and annealing, and this step is repeated to improve the crystalline quality and thickness of the film.

Benefits of technology

By improving the crystal quality and thickness of the perovskite film, the efficient utilization of indoor photons and the improvement of photoelectric conversion efficiency are achieved, and the carrier diffusion length needs in thick films are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562734A_ABST
    Figure CN119562734A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a perovskite cell. The preparation method comprises the following steps: evaporation: evaporating a CsPbI2Br film on an electron transport layer or a hole transport layer; wherein the electron transport layer or the hole transport layer is arranged on the transparent conductive electrode; soaking: soaking the CsPbI2Br thin film in an additive solution; annealing: carrying out annealing treatment on the soaked CsPbI2Br thin film; repeating the steps of evaporation, soaking and annealing on the annealed CsPbI2Br thin film; and preparing a hole transport layer / metal electrode or an electron transport layer / metal electrode on the last layer of CsPbI2Br thin film to obtain a formal perovskite cell or a trans perovskite cell. Compared with a traditional one-step forming process, the multi-step circulating evaporation method provided by the invention has the advantages that an additive can be used for assisting crystallization to act in the perovskite thin film in a penetrating manner, so that the crystallization quality of the thin film is improved; any thickness adjustment can be realized, efficient utilization of indoor photons is realized, and the photoelectric conversion efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite batteries, and in particular relates to a method for preparing a perovskite battery. Background Art

[0002] With the development of industrial Internet of Things, smart home and smart travel, the demand for efficient collection of indoor weak light using photovoltaic cells is growing. Usually, indoor light sources have a large proportion of long-wavelength photons, which require a thicker light-absorbing layer to achieve complete absorption. 2 Br has a high indoor LED light conversion efficiency due to its suitable band gap, but the solubility of inorganic salts in conventional DMF and DMSO is poor and it is limited by the concentration of the precursor solution, so the thickness of the obtained perovskite film is difficult to increase.

[0003] At present, the solution method is commonly used to prepare perovskite films. However, CsBr and CsI have low solubility in organic solvents DMF and DMSO. The solubility in a conventional mixed solvent with a volume ratio of DMF:DMSO of 4:1 is less than 1 mol / L, and the thickness of the prepared film is usually less than 600 nm (e.g., Zhanglin Guo.Dopant-Free Polymer HTM-Based CsPbI 2 Br SolarCells with Efficiency Over 17% in Sunlight and 34% in Indoor Light[J].Adv.Funct.Mater.2021,31,2103614.(Thickness 500nm) and Shan Jiang.EfficientPerovskite Indoor Photovoltaics with Open-Circuit Voltage of 1.15V via Collaborative Optimization of CsPbI 2 Br Layer and Hole Transport Layer[J].Small methods.2022,6,2200624.(thickness is about 500nm)). Existing technology only optimizes film quality at this thickness, but the theoretical upper limit efficiency is low.

[0004] Vacuum thermal evaporation is a common method for dry preparation of perovskite materials, which can avoid the solubility shortcomings of solvents (such as the preparation of stable CsPbI based on high-throughput gas phase co-evaporation disclosed in Chinese patent (publication number CN114686811A) 2Br inorganic perovskite film method), and by extending the evaporation time, a film of any thickness can be obtained. However, thick perovskite films place higher requirements on the carrier diffusion length (the carrier diffusion length needs to be greater than the film thickness).

[0005] At present, CsPbI is prepared by evaporation method 2 Br thin films are usually formed in one piece (e.g., Qingshan Ma, Shujuan Huang. The Effect of Stoichiometry on the Stability of Inorganic Cesium Lead Mixed-Halide Perovskites Solar Cells[J]. J. Phys. Chem. C. 2017, 121, 36, 19642-19649), and it is difficult to control the crystal quality inside the film. Summary of the invention

[0006] In view of the above problems, the present invention discloses a method for preparing a perovskite battery, comprising the following steps:

[0007] Evaporation: Evaporation of CsPbI on the electron transport layer or hole transport layer 2 Br film; wherein the electron transport layer or the hole transport layer is arranged on the transparent conductive electrode;

[0008] Soaking: The CsPbI 2 Br film is immersed in the additive solution;

[0009] Annealing: The CsPbI 2 The Br film is annealed;

[0010] After annealing, the CsPbI 2 Repeat the above evaporation, immersion and annealing steps on the Br film;

[0011] In the last layer, the CsPbI 2 A hole transport layer / metal electrode or an electron transport layer / metal electrode is prepared on the Br film to obtain a formal perovskite cell or an inverse perovskite cell.

[0012] Furthermore, the evaporation is: evaporating CsPbI on the electron transport layer or the hole transport layer 2 Br film also includes:

[0013] Preparing an electron transport layer on a transparent conductive electrode; or

[0014] A hole transport layer is prepared on the transparent conductive electrode.

[0015] Furthermore, the CsPbI 2 Br thin film using PbI 2 , CsBr dual-source co-evaporation method;

[0016] Among them, PbI 2 The evaporation rate Evaporation rate of CsBr

[0017] Single-layer CsPbI 2 The thickness of the Br film is 100-300 nm.

[0018] Furthermore, the CsPbI 2 The total thickness of the Br film is 500-1500 nm.

[0019] Furthermore, the CsPbI 2 The specific steps of immersing the Br film in the additive solution are as follows:

[0020] CsPbI 2 The Br film was immersed in 0.5-2 mg / ml additive solution for 20-30 s.

[0021] Furthermore, the additive is MACl, FACl, MASCN, FASCN, Pb(SCN) 2 NH 4 SCN, NH 4 At least one of Cl, urea, thiourea, methylaminoacetic acid, and thiosemicarbazide.

[0022] Furthermore, the CsPbI 2 The specific steps of annealing the Br film are as follows:

[0023] After soaking, CsPbI 2 The Br film is placed on a high temperature heating stage and annealed at 100-300°C for 10-20 min.

[0024] Furthermore, the CsPbI 2 The specific steps of repeating the above evaporation, immersion and annealing steps on the Br film are as follows:

[0025] CsPbI after annealing 2 Repeated evaporation of CsPbI on Br film 2 Br film, the CsPbI 2 Br film is immersed in the additive solution and the CsPbI 2 Br film is annealed.

[0026] Furthermore, the preparation method of the hole transport layer in the formal perovskite cell is as follows:

[0027] Spin coat 10-20 mg / ml P3HT solution on CsPbI 2 On Br film;

[0028] Then, the substrate is heated at 80-120°C for 10-20 minutes; wherein the spin coating condition is 3000-6000 r / min, and the rotation time is 20-60 seconds;

[0029] The preparation method of the hole transport layer in the inverse perovskite cell is as follows:

[0030] 5-10 nm nickel oxide nanoparticles are dispersed in deionized water at a concentration of 10-30 mg / ml, spin-coated on a transparent conductive electrode, and then annealed at 80-150°C for 10-30 min;

[0031] The thickness of nickel oxide is 20-30 nm; the spin coating condition is 3000-5000 r / min, and the rotation is 20-40 s.

[0032] Furthermore, the preparation method of the metal electrode is as follows:

[0033] Vapor deposit 80-150nm thick Au or Cu on the surface of the hole transport layer or the electron transport layer;

[0034] Among them, the thermal evaporation rate of Au or Cu is

[0035] Compared with the prior art, the embodiments of the present invention have at least the following advantages:

[0036] 1. Compared with the traditional one-step forming process, the multi-step cycle evaporation method provided by the present invention can make the additive-assisted crystallization act throughout the perovskite film to improve the crystallization quality of the film;

[0037] 2. It can realize arbitrary thickness adjustment, realize efficient utilization of indoor photons, and improve photoelectric conversion efficiency.

[0038] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 A flow chart of a method for preparing a perovskite battery according to an embodiment of the present invention is shown. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The realization of higher efficiency of perovskite cells should be based on thicker light-absorbing layer thickness, so thickness control is one of the purposes of the present invention. The quality of thick film is a key factor in determining the carrier diffusion length, so improving the quality of thick film becomes the second purpose of the present invention.

[0043] The present invention adopts multi-step evaporation of CsPbI 2 The Br-spin coating / immersion additive method improves the crystallization quality of thick films.

[0044] Figure 1 FIG. 1 is a flow chart showing a method for preparing a perovskite battery according to an embodiment of the present invention. Figure 1 As shown, a method for preparing a perovskite battery proposed in the present invention specifically comprises the following steps:

[0045] Evaporation: Evaporation of CsPbI on the electron transport layer or hole transport layer 2 Br film; wherein the electron transport layer or the hole transport layer is arranged on the transparent conductive electrode;

[0046] Soaking: The CsPbI 2 Br film is immersed in the additive solution;

[0047] Annealing: The CsPbI 2 The Br film is annealed;

[0048] After annealing, the CsPbI 2 Repeat the above evaporation, immersion and annealing steps once or multiple times on the CsPbI Br film; that is, after annealing,2 Repeated evaporation of CsPbI on Br film 2 Br film, the CsPbI 2 Br film is immersed in the additive solution and the CsPbI 2 The Br film is annealed;

[0049] In the last layer, the CsPbI 2 A hole transport layer / metal electrode or an electron transport layer / metal electrode is prepared on the Br film to obtain a formal perovskite cell or an inverse perovskite cell.

[0050] Among them, the battery structure of the formal perovskite battery: transparent conductive electrode / electron transport layer / CsPbI 2 Br / hole transport layer / metal electrode, such as FTO / TiO 2 / CsPbI 2 Br / P3HT / Au;

[0051] The cell structure of the inverse perovskite cell: transparent conductive electrode / hole transport layer / CsPbI 2 Br / electron transport layer / metal electrode, such as FTO / NiOx / CsPbI 2 Br / C60 / BCP / Cu.

[0052] In some embodiments, the last layer of CsPbI is evaporated 2 Br film, the above evaporation and annealing steps can also be repeated only once without immersing the additive, that is, after the annealing treatment, the CsPbI 2 Repeated evaporation of CsPbI on Br film 2 Br thin film, CsPbI 2 Br film is annealed.

[0053] In some embodiments, the last layer of CsPbI 2 After the Br film is annealed, it can be selectively surface treated, such as using 5-aminopentanoic acid hydrobromide or δ-2:2-bis(1,3-dithiazole) (interface modification) for surface treatment.

[0054] Compared with the traditional one-step forming process, the multi-step cyclic evaporation method provided by the present invention can allow the additive-assisted crystallization to act throughout the perovskite film, thereby improving the crystallization quality of the film.

[0055] The perovskite cell prepared by the method of the present invention can be used under indoor light and can also be extended to any light source such as the solar spectrum.

[0056] The preparation method of the present invention is used to improve the quality of high-thickness perovskite films prepared by evaporation, and is not limited to CsPbI2 Br is a component.

[0057] In some embodiments, evaporation: evaporation of CsPbI on the electron transport layer or the hole transport layer 2 Br film also includes:

[0058] Preparing an electron transport layer on a transparent conductive electrode; or

[0059] A hole transport layer is prepared on the transparent conductive electrode.

[0060] The specific steps of preparing an electron transport layer on a transparent conductive electrode are as follows:

[0061] Place FTO conductive glass in 0.15-0.25M TiCl 4 In aqueous solution, react at 60-80℃ for 0.5-1.5h, and rinse with deionized water after the reaction;

[0062] Then anneal at 200-500℃ for 1-2h to obtain FTO / TiO 2 .TiO 2 The thickness is 100-200nm.

[0063] The above method can realize low temperature preparation of TiO 2 Compared with the TiO prepared by spin coating 2 Better uniformity.

[0064] Although the electron transport layer is TiO 2 The electron transport layer may be made of other materials, such as ZnO, SnO 2 Those skilled in the art may make a comprehensive consideration based on the purpose of the present invention and actual application, as long as stable and rapid transmission of electrons can be achieved.

[0065] In some embodiments, the CsPbI 2 Br thin film using PbI 2 , CsBr dual-source co-evaporation method;

[0066] Among them, PbI 2 The evaporation rate Evaporation rate of CsBr The above evaporation rates can ensure the compositional purity of the film components.

[0067] Single-layer CsPbI 2 The thickness of the Br film is 100-300 nm.

[0068] In some embodiments, the perovskite battery contains CsPbI2 The total thickness of the Br film is 500-1500nm. CsPbI 2 When the total thickness of the Br film is set to 500-1500nm, the film thickness is thicker than that prepared by the existing conventional scheme, which can achieve a greater degree of absorption of incident light and a higher short-circuit current density of the device.

[0069] CxP 2 The bandgap of the Br film is 1.88-1.93 eV, which can ensure that the light absorption range of the perovskite cell is more closely matched to the spectral range of indoor LED light.

[0070] In some embodiments, the CsPbI 2 The specific steps of immersing the Br film in the additive solution are as follows:

[0071] At room temperature, CsPbI 2 The Br film is immersed in a 0.5-2 mg / ml additive solution for 20-30 seconds. The solvent of the additive solution can be isopropanol. The above conditions are used for immersion treatment to make the additive more easily attached to CsPbI 2 Br film.

[0072] Although the present invention is illustratively described by taking immersion in an additive solution as an example, the present invention is not limited thereto, and the additive solution may also be applied by a slit coating method, a doctor blade coating method, a solution spin coating method, and the like.

[0073] In some embodiments, the additive is MACl, FACl, MASCN, FASCN, Pb(SCN) 2 NH 4 SCN, NH 4 At least one of Cl, urea, thiourea, methylamine acetic acid, and semicarbazide. The perovskite film is treated with the above additives to increase the density of the perovskite film, increase the size of the grains, and enhance the crystal quality.

[0074] In some embodiments, the soaked CsPbI 2 The specific steps of annealing the Br film are as follows:

[0075] After soaking, CsPbI 2 The Br film is placed on a high temperature heating table and annealed at 100-300°C for 10-20 minutes. Annealing under the above conditions can enhance the CsPbI 2 Crystalline quality of Br films.

[0076] This article takes a heating stage as an example for illustrative description, but the present invention is not limited to this. The annealing treatment can also be carried out by oven heating, laser-assisted annealing and other methods.

[0077] It should be noted that the annealing treatment can be performed after each step of the additive treatment, or after repeated evaporation-solution cycles, or after combining several cycles.

[0078] In some embodiments, the preparation method of the hole transport layer in the formal perovskite cell is as follows:

[0079] Spin coat 10-20 mg / ml P3HT solution on CsPbI 2 Br film; exemplarily, the solvent of the P3HT solution may be chlorobenzene;

[0080] Then heat at 80-120℃ for 10-20min;

[0081] The spin coating conditions are 3000-6000 r / min, and the rotation is 20-60 s.

[0082] The thickness of the hole transport layer is 20-60 nm.

[0083] Although P3HT is used as an example of a hole transport layer in the above description, the present invention is not limited thereto, and a variety of other hole transport materials, such as Spiro-OMeTAD and PTAA, may be used.

[0084] In some embodiments, the preparation method of the hole transport layer in the inverse perovskite cell is as follows:

[0085] 5-10 nm nickel oxide nanoparticles are dispersed in deionized water at a concentration of 10-30 mg / ml, spin-coated on a transparent conductive electrode, and then annealed at 80-150°C for 10-30 min;

[0086] The thickness of nickel oxide is 20-30 nm; the spin coating condition is 3000-5000 r / min, and the rotation is 20-40 s.

[0087] Although nickel oxide is used as an example above, the hole transport layer in the inverse perovskite battery is not limited to nickel oxide, and materials such as PTAA and monolayer can also be used.

[0088] In some embodiments, the preparation method of the metal electrode is as follows:

[0089] Evaporate 80-150nm thick Au or Cu on the hole transport layer of the formal perovskite cell or the electron transport layer of the inverse perovskite cell;

[0090] Among them, the thermal evaporation rate of Au or Cu is

[0091] Although Au is used as the metal electrode as an example for illustrative description herein, the present invention is not limited thereto, and a variety of other metal materials, such as Ag, Cu, Al, etc., may be used.

[0092] The preparation method of the electron transport layer of the inverse perovskite cell is as follows:

[0093] C60 (fullerene) powder is deposited on the perovskite film by evaporation coating, and the evaporation rate is Thickness 20-30nm.

[0094] The electron transport layer of the inverse perovskite battery can also be made of materials such as PCBM and tin oxide.

[0095] The present invention is illustratively described by taking the preparation of a formal perovskite battery as an example.

[0096] Example 1

[0097] A method for preparing a perovskite battery is as follows:

[0098] FTO conductive glass was placed in 0.2M TiCl 4 The reaction was carried out in an aqueous solution at 70 °C for 1 h, and then rinsed with deionized water; then annealed at 500 °C for 1 h to obtain FTO / TiO 2 ;

[0099] Using PbI 2 , CsBr dual-source co-evaporation method in FTO / TiO 2 Preparation of CsPbI on the surface 2 Br film; among them, PbI 2 The evaporation rate Evaporation rate of CsBr

[0100] Single-layer CsPbI 2 The thickness of the Br film is 300 nm;

[0101] FTO / TiO 2 / CsPbI 2 Br was immersed in IPA solvent with a MACl concentration of 2 mg / ml for 30 s to allow the additive to adhere to the surface of the perovskite film;

[0102] The immersed FTO / TiO 2 / CsPbI 2 Br was placed on a high temperature heating table and annealed at 260°C for 20 min;

[0103] After annealing, FTO / TiO 2 / CsPbI 2Br surface with PbI 2 Preparation of the second layer of CsPbI by dual-source co-evaporation of CsBr 2 Br film; among them, PbI 2 The evaporation rate Evaporation rate of CsBr

[0104] FTO / TiO 2 / CsPbI 2 Br was immersed in IPA solvent with a MACl concentration of 2 mg / ml for 30 s to allow the additive to adhere to the surface of the perovskite film;

[0105] The immersed FTO / TiO 2 / CsPbI 2 Br was placed on a high temperature heating table and annealed at 260°C for 20 min;

[0106] Single-layer CsPbI 2 The thickness of the Br film is 300nm; the two layers of CsPbI 2 The total thickness of the Br film is 600nm; CsPbI 2 The band gap of Br film is 1.91 eV;

[0107] 15 mg / ml P3HT solution was spin-coated on FTO / TiO 2 / CsPbI 2 Br surface, and then heated at 100 °C for 10 min;

[0108] The spin coating condition was 5000r / min, and the rotation was 30s. The thickness of the hole transport layer was 40nm, and FTO / TiO 2 / CsPbI 2 Br / P3HT;

[0109] In FTO / TiO 2 / CsPbI 2 100 nm of Au was evaporated on the surface of Br / P3HT to obtain a perovskite cell; the thermal evaporation rate of Au is

[0110] Example 2

[0111] A method for preparing a perovskite battery, the steps are the same as those in Example 1, except that 300 nm of CsPbI is first evaporated 2 Br film, then immersed in 2mg / ml MACl solution, annealed, and then evaporated 300nm CsPbI 2Br film, then immersed in 2mg / ml MACl solution, annealed, and then evaporated 300nm CsPbI 2 Br film, and then immersed in 2mg / ml MACl solution for annealing. CsPbI 2 The total thickness of Br is 900nm and the bandgap is 1.90eV.

[0112] Example 3

[0113] A method for preparing a perovskite battery, the steps are the same as those in Example 1, except that 300 nm of CsPbI is evaporated 2 Br film, then immersed in 2mg / ml MACl solution, annealed, and then evaporated 300nm CsPbI 2 Br film, then immersed in 2mg / ml MACl solution, annealed, and then evaporated 300nm CsPbI 2 Br film, then immersed in 2mg / ml MACl solution, annealed, and then evaporated 300nm CsPbI 2 Br film, and then immersed in 2mg / ml MACl solution for annealing, CsPbI 2 The total thickness of Br is 1200nm and the bandgap is 1.90eV.

[0114] Comparative Example 1

[0115] A method for preparing a perovskite battery, the steps are the same as those in Example 1, except that 600nm of CsPbI is directly evaporated 2 Br film without immersion in additive solution, CsPbI 2 The band gap of Br film is 1.91eV.

[0116] Comparative Example 2

[0117] A method for preparing a perovskite battery, the steps are the same as those in Example 1, except that 900nm of CsPbI is directly evaporated 2 Br film without immersion in additive solution, CsPbI 2 The band gap of Br film is 1.92eV.

[0118] Comparative Example 3

[0119] A method for preparing a perovskite battery, the steps are the same as those in Example 1, except that 1200nm of CsPbI is directly evaporated 2 Br film without immersion in additive solution, CsPbI 2 The band gap of Br film is 1.91eV.

[0120] The performance of the perovskite cells prepared in the above embodiments and comparative examples was tested respectively. The specific test data are shown in Table 1. It can be seen from Table 1 that for the CsPbI 2 Br film, using the additive step-by-step evaporation method, the battery PCE efficiency is higher, and the battery Jsc / Voc / FF are significantly improved; in the vertical comparison of the comparative example, with the CsPbI 2 As the thickness of the Br film increases, the Jsc of the battery increases, but the Voc and FF decrease, indicating that the internal crystal quality of the thick perovskite film deteriorates and the carrier transport is hindered. The reduction of Voc and FF in the embodiment is slowed down, proving that the internal crystal quality of the perovskite film is significantly improved.

[0121] Table 1 Test data

[0122] <![CDATA[Jsc(μA·cm -2 )]]> Voc(V) FF(%) PCE(%) Example 1 114.3 0.99 81.4 28.0 Example 2 119.2 0.98 81.0 28.8 Example 3 122.7 0.97 80.3 29.1 Comparative Example 1 105.8 0.92 79.3 23.4 Comparative Example 2 109.3 0.90 75.2 22.5 Comparative Example 3 113.2 0.87 70.5 21.1

[0123] The photovoltaic parameter test conditions of the perovskite cell in the embodiment and the comparative example are: illumination 1000 lux, incident light power 329 μW·cm -2 .

[0124] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In the present invention, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine different embodiments or examples described in the present invention and features of different embodiments or examples without contradiction.

[0125] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a perovskite battery, characterized in that: The following steps are involved: Evaporation: Evaporating a CsPbI2Br thin film on the electron transport layer or the hole transport layer; wherein the electron transport layer or the hole transport layer is disposed on the transparent conductive electrode; Soaking: Soaking the CsPbI2Br film in an additive solution; Annealing: annealing the CsPbI2Br film after immersion; Repeating the above-mentioned evaporation, immersion and annealing steps on the CsPbI2Br film after annealing; A hole transport layer / metal electrode or an electron transport layer / metal electrode is prepared on the last layer of the CsPbI2Br film to obtain a formal perovskite cell or an inverse perovskite cell.

2. The method for preparing a perovskite battery according to claim 1, characterized in that: The evaporation: before evaporating the CsPbI2Br film on the electron transport layer or the hole transport layer, the process also includes: Preparing an electron transport layer on a transparent conductive electrode; or A hole transport layer is prepared on the transparent conductive electrode.

3. The method for preparing a perovskite battery according to claim 1, characterized in that: The CsPbI2Br film is prepared by a method of co-evaporation of PbI2 and CsBr; Among them, the evaporation rate of PbI2 Evaporation rate of CsBr The thickness of the single-layer CsPbI2Br film is 100-300nm.

4. The method for preparing a perovskite battery according to claim 1, characterized in that: The total thickness of the CsPbI2Br film in the perovskite cell is 500-1500nm.

5. The method for preparing a perovskite battery according to claim 1, characterized in that: The specific steps of immersing the CsPbI2Br film in the additive solution are as follows: Soak the CsPbI2Br film in 0.5-2 mg / ml additive solution for 20-30 s.

6. The method for preparing a perovskite battery according to claim 5, characterized in that: The additive is at least one of MACl, FACl, MASCN, FASCN, Pb(SCN)2, NH4SCN, NH4Cl, urea, thiourea, methylamine acetic acid, and semicarbazide.

7. The method for preparing a perovskite battery according to claim 1, characterized in that: The specific steps of annealing the immersed CsPbI2Br film are as follows: The soaked CsPbI2Br film is placed on a high temperature heating table and annealed at 100-300°C for 10-20min.

8. The method for preparing a perovskite battery according to claim 1, characterized in that: The specific steps of repeating the above-mentioned evaporation, immersion and annealing steps on the CsPbI2Br film after annealing are as follows: Repeating the steps of evaporating a CsPbI2Br film on the annealed CsPbI2Br film, immersing the CsPbI2Br film in an additive solution, and annealing the immersed CsPbI2Br film.

9. The method for preparing a perovskite battery according to claim 1, characterized in that: The preparation method of the hole transport layer in the formal perovskite cell is as follows: 10-20 mg / ml P3HT solution was spin-coated on the CsPbI2Br film; Then, the substrate is heated at 80-120°C for 10-20 minutes; wherein the spin coating condition is 3000-6000 r / min, and the rotation time is 20-60 seconds; The preparation method of the hole transport layer in the inverse perovskite cell is as follows: 5-10 nm nickel oxide nanoparticles are dispersed in deionized water at a concentration of 10-30 mg / ml, spin-coated on a transparent conductive electrode, and then annealed at 80-150°C for 10-30 min; The thickness of nickel oxide is 20-30 nm; the spin coating condition is 3000-5000 r / min, and the rotation is 20-40 s.

10. The method for preparing a perovskite battery according to claim 1, characterized in that: The preparation method of the metal electrode is as follows: Vapor deposit 80-150nm thick Au or Cu on the surface of the hole transport layer or the electron transport layer; Among them, the thermal evaporation rate of Au or Cu is

Citation Information

Patent Citations

  • Preparation method and application of chlorine-based wide-band-gap perovskite light absorption layer

    CN111180580A

  • Carbon-based mesoscopic perovskite solar cell based on urea or derivative additive thereof and preparation method of carbon-based mesoscopic perovskite solar cell

    CN113555505A

  • Bandgap-tunable perovskite materials and methods of making the same

    US20190062175A1

  • Method of bandgap tuning of co-evaporated perovskite

    WO2023003519A2